2006
DOI: 10.1055/s-2005-915587
|View full text |Cite
|
Sign up to set email alerts
|

Die sensible Atemwegsinnervation und die Tachykinine bei Asthma und chronisch-obstruktiver Lungenerkrankung (COPD)

Abstract: The airway nerve has gained importance in the field of respiratory research as it is known to have the capacity to release numerous mediators which can cause pulmonary effects in the airways. Meanwhile, a broad range of stimuli including capsaicin, bradykinin, hyperosmolar saline, tobacco smoke, allergens, ozone, inflammatory mediators and cold dry air have been shown to activate sensory nerve fibres to release neuropeptides such as the tachykinins substance P (SP) and neurokinin A (NKA) to mediate neurogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, the ability to induce cough has since been contested 62 . Like SP, NKA induces bronchoconstriction and mucus production in the lungs as well as neurogenic inflammation 63 . Additionally, NKA is a potent attractor of T-cells 57 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to induce cough has since been contested 62 . Like SP, NKA induces bronchoconstriction and mucus production in the lungs as well as neurogenic inflammation 63 . Additionally, NKA is a potent attractor of T-cells 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurokinins (NKs) are peptides synthesized by neural tissues that have been implicated as the mediators of neurogenic inflammation in asthma. NKs have potent effects on airway smooth muscle tone, airway secretion, bronchial circulation, and inflammatory and immune cells via the activation of the neurokinin-1 (NK-1R) and neurokinin-2 receptors (NK-2R); as such, they have been proposed to play an important role in human respiratory conditions such as bronchial asthma and chronic obstructive diseases [2]. For example, Pattersson et al demonstrated that tachykinin levels were increased in induced sputum from patients with asthma, cough, and acid reflux [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tachykinins have been proposed to play an important role in human respiratory diseases such as bronchial asthma and chronic obstructive pulmonary diseases (COPD), as they have been shown to activate the neurokinin (NK)-1 and NK-2 receptors, leading to potent effects on airway smooth muscle tone and secretions, bronchial circulation, and inflammatory and immune cells [10]. Tachykinin levels were increased in induced sputum from asthmatic and cough patients with acid reflux [11].…”
Section: Introductionmentioning
confidence: 99%